2012
DOI: 10.1073/pnas.1208698109
|View full text |Cite
|
Sign up to set email alerts
|

Apoptotic and antitumor activity of death receptor antibodies require inhibitory Fcγ receptor engagement

Abstract: By virtue of their ability to induce apoptosis and regulate growth, differentiation, and cytokine responses, the tumor necrosis factor receptor (TNFR) superfamily members have emerged as attractive targets for anticancer therapeutics. Agonistic antibodies to apoptosisinducing TNFRs, such as death receptor 5 (DR5), although displaying impressive activities against a variety of tumors in preclinical models, appear to be less active in clinical trials. We report that the in vivo apoptotic and antitumor activities… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
97
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 92 publications
(103 citation statements)
references
References 43 publications
5
97
1
Order By: Relevance
“…Many tumor necrosis factor receptor (TNFR) superfamily members such as CD40 and DR5 control key signaling pathways involved in immune and antitumor responses, and agonistic antibodies targeting these molecules have shown promising antitumor activities in preclinical studies (13). We and others have recently found that both agonistic αCD40 and αDR5 antibodies require Fc-FcγR interactions for their in vivo activities and, in contrast to cytotoxic effector antitumor antibodies, these agonistic antibodies require no activating FcγRs, but inhibitory FcγRIIB (14)(15)(16). These studies, together with previous and other recent studies (17,18), have established a general requirement of FcγRIIB for the in vivo activities of agonistic anti-TNFR antibodies (19).…”
mentioning
confidence: 69%
See 4 more Smart Citations
“…Many tumor necrosis factor receptor (TNFR) superfamily members such as CD40 and DR5 control key signaling pathways involved in immune and antitumor responses, and agonistic antibodies targeting these molecules have shown promising antitumor activities in preclinical studies (13). We and others have recently found that both agonistic αCD40 and αDR5 antibodies require Fc-FcγR interactions for their in vivo activities and, in contrast to cytotoxic effector antitumor antibodies, these agonistic antibodies require no activating FcγRs, but inhibitory FcγRIIB (14)(15)(16). These studies, together with previous and other recent studies (17,18), have established a general requirement of FcγRIIB for the in vivo activities of agonistic anti-TNFR antibodies (19).…”
mentioning
confidence: 69%
“…These studies, together with previous and other recent studies (17,18), have established a general requirement of FcγRIIB for the in vivo activities of agonistic anti-TNFR antibodies (19). In addition, we have also demonstrated that Fcs that preferentially bind to inhibitory FcγRIIB are more potent for agonistic anti-TNFR antibodies, and that the potency of agonistic anti-TNFR antibodies can be enhanced through FcγRIIB-targeted Fc engineering (14,15). Although these studies have provided a logical approach to designing potent agonistic anti-TNFR antibodies, the in vivo mechanism underlying this general FcγRIIB requirement remains to be determined.…”
mentioning
confidence: 70%
See 3 more Smart Citations